A dynamical approach to quantitative precipitation forecast (MAUSAM, 1986)
A method for quantitative precipitation forecast has been suggested. The precipitation rates are assumed to be directly proportional to large-scale vertical velocity. The constant of proportionately is a function of temperature, pressure and moisture contents or more specifically of difference between dry and saturated adiabatic lapse rates. Using the method, precipitation rates have been calculated for a specific synoptic situation and compared with the observed rainfall.